Evaluating blended learning effectiveness: an empirical study from undergraduates’ perspectives using structural equation modeling - Han, Xiaotian (Frontiers in Psychology, 2023)
Following the global COVID-19 outbreak, blended learning (BL) has received increasing attention from educators. The purpose of this study was: (a) to develop a measurement to evaluate the effectiveness of blended learning for undergraduates; and (b) to explore the potential association between effectiveness with blended learning and student learning outcomes. This research consisted of two stages. In Stage I, a measurement for evaluating undergraduates’ blended learning perceptions was developed. In Stage II, a non-experimental, correlational design was utilized to examine whether or not there is an association between blended learning effectiveness and student learning outcomes. SPSS 26.0 and AMOS 23.0 were utilized to implement factor analysis and structured equation modeling. The results of the study demonstrated: (1) The hypothesized factors (course overview, course objectives, assessments, 1148 class activities, course resources, and technology support) were aligned as a unified system in blended learning. (2) There was a positive relationship between the effectiveness of blended learning and student learning outcomes. Additional findings, explanations, and suggestions for future research were also discussed in the study.